PERANAN MASYARAKAT DALAM PENGEMBANGAN OBJEK WISATA ALAM DANAU NINIFALA DESA PILIANA KABUPATEN MALUKU TENGAH - Yusdi Y.R.S Mahulete; Henderina Lelloltery; Billy B. Seipalla (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2020)
The objectives of this study were to identify the potential of natural tourism of Lake Ninifala and determine the communities roles on managing and developing Lake Ninifala tourism object. The method used was survey with interview, observation, and documentation data collection techniques. Community sampling was used purposive sampling technique. Analysis of the data used descriptive qualitative analysis. The results showed the potential of the lake ninifala tourism object, including the potential of flora and fauna which has the uniqueness and natural beauty in the form of two trees in the middle of the lake called